Pengabdian Masyarakat Tentang Inovasi Pemanfaatan Limbah Kopi Untuk Meningkatkan Sanitasi Lingkungan - Razi, T. Khairol; Maifrizal; Wahidanur; Salahudin, Muhammad; Maulida, Dara; Luciana, Lisma; Megawati; Yusnita; Yulidar; Syahbuddin; Hijriana, Isni; Syahputra, Fadli (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
Coffee husk waste is a type of agricultural waste that is often overlooked and accumulates around coffee production areas. Although often considered trash, this waste has enormous potential if managed properly and correctly, and can even provide economic and environmental benefits. This training is part of a community service program aimed at promoting environmentally friendly and sustainable waste management practices. The success of this program is expected to serve as a model for other regions facing similar challenges in waste management and improving the welfare of their communities. The target group is the community in the coffee production center at the Baitul Qiradh Baburrayyan Cooperative, as well as groups of housewives and communities involved in coffee processing activities. The activities include: Socialization and Education, Training on Coffee Waste Management Innovation, and Mentoring and Monitoring. It is recommended that ongoing support from the local government and the private sector be provided to expand the implementation of innovations. The community is expected to continue practicing coffee waste processing and make it part of an environmentally friendly lifestyle.